ANALISIS KELULUSAN SMA NEGERI DI KABUPATEN KEPULAUAN MENTAWAI, 2009-2014 - , JUSTAMAR KAMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Education plays an important role in promoting the quality of peopleâs life. The level of peopleâs education determine the acceleration of development process in a country. The level of Mentawai people is categorized still low. One of the indicators is only 2.66 percentage of Mentawai people who graduate from university or college. The level of student graduates is influenced by many factors, such as: teachers, facilities, the role of parents and society, and budget. The study focuses on impact of teachers and student-teacher ratio for increasing student graduates rate of state senior high school in Mentawai Islands Regency. The purpose of the study is to analyze the impact of number of teachers who have S-1 degree, number of certified teachers, number of teachers who teach more than one subject, and student-teacher ratio toward the number of student graduates. All state senior high school in Mentawai Islands Regency is the population of the study in 2008/2009-2013/2014 academic year. The data used in the study is acquired from Mentawai Education Office, then analyzed by panel data regression. The result of analysis shows that the number of teachers who have S-1 degree has positive impact significantly in increasing the number of student graduate at the state senior high school in Mentawai Islands Regency. The student-teacher ratio variable also has positive influence significantly in increasing the number of student graduate at the state senior high school. Keywords: student graduates, number of teachers who have S-1 degree, certified teacher, student-teacher ratio.